Comparative Study of Different Controllers for Levitating Ferromagnetic Material. (20th May 2022) - Deepa, T.; Subbulekshmi, D.; Lakshmi, P.; Maheedhar, Marabathina; Kishore, E.; Vinodharanai, M.; Chockalingam, T.
Abstract : The purpose of the analysis is to levitate and stabilize a spherical ball of magnetic levitation system at the desired position using various controllers and determine the one which gives better performance. The ball which is used to levitate is a ferromagnetic material such as stainless steel. This study talks about the proportional derivative controller, proportional integral derivative (PID) controller, and linear quadratic regulator (LQR) controller in place of a physical system. The transient response of the magnetic levitation system can be modified for desirable results due to the implementation of the controller. Simulation and experimental methods are used to verify the results. Both the techniques have been made to stabilize the ball position in the desired position. PID and LQR are designed to achieve the ball position to the desired level, and it is observed that the LQR controller gives the best result.